Temporal Exponential Random Graph Models with btergm: Estimation and Bootstrap Confidence Intervals - Philip Leifeld (Journal of Statistical Software, 2018)
The xergm package is an implementation of extensions to the exponential random graph model (ERGM). It acts as a meta-package for multiple constituent packages. One of these packages is btergm, which implements bootstrap methods for the temporal ERGM estimated by maximum pseudolikelihood. Here, we illustrate the temporal exponential random graph model and its implementation in the package btergm using data on international alliances and a longitudinally observed friendship network in a Dutch school.